ONLINE CRIMINAL CLINIC (Proceedings of the International Conference on Education, 2021)
Confinement brought with it virtual classes, and that teaching channel that was once the exception, became the rule, but, what are the implications that this change produced for crime victims who seek access to justice?The main objective of this contribution is to exemplify, by sharing the results and experiences produced by the criminal clinic taught in virtual format of the Campus Puebla, how online clinical teaching, as well as a face-to-face legal clinic execution, achieves a differentiated learning in relation to the traditional methodology of teaching, that is, the development of disciplinary and transversal educational competences for criminal litigation through experiential learning.The penal clinic at the Tecnológico de Monterrey in Puebla City, Mexico, was established four years ago from the project "Voice of the Victims" in conjunction with the Arizona State University and sponsored by the Merida Initiative. The criminal clinic works with an external institution called "socio-trainer".By acquiring knowledge about the role of legal advisors to victims, and by taking an active part in the entire criminal process, students develop diverse transversal competences like professional responsibility, human sense, and professional ethics; In addition to that, this contribution aims to also showcase the online criminal clinic execution limitations and opportunities of development when compared to the face-to-face or in person clinic development.The methodology follows a format of assigning real criminal cases to students who assume the role of victim lawyers; They are guided by professors from the University and a lawyer from the Socio-trainer Institution. They are evaluated according to the procedural progress of the assigned cases, as well as activities and alternatives for access to justice such as: counseling for crime victims, preparation of briefs and guidelines for hearings. In the August-December 2020 semester, the clinic was executed online, and the methodology underwent an important transformation in its academic and practical aspects, as well as in the care and follow-up of assigned criminal cases. The process had negative implications due to the lack of constant interaction with the victims and the authorities, but this did not substantially affect the student's learning.
Keywords: Victims; Criminal Cases; Criminal Process; Clinical teaching; Online Education